PENGETAHUAN IBU PRIMIPARA TENTANG FAKTOR-FAKTOR YANG DAPAT MEMPENGARUHI PRODUKSI ASI - Rizka Yulianti Rahayu; Sari Sudarmiati (Jurusan Keperawatan, Universitas Diponegoro, 2012)
Infant mortality in Indonesia is still high. That is due to serious disease problems. One way to anticipate serious disease’s attack that is increasing the body's immune baby with breast-feeding infants. Obstruction of breastmilk production in primiparous mother become one of problem in Tugurejo Hospital. The purpose of this study to assess knowledge of primiparous mothers about factors that may affect milk production. Type of this research was quantitative research, which was a descriptive survey. The method used of this research was cross sectional. Population of this research is all of primiparous mother in Room Bougenville Tugurejo Hospital Semarang. The research used total sampling with 60 respondents. The result of this study showed that knowledge of primiparous mothers was good and enough, but there were primiparous mother that had less and not good knowledge in factor nutrition, rest and sleep, oxytocin message, used of contraceptive, and breastfeeding technique. That’s why, primiparous mother need to increase more information about the way can product breastmilk